Spectroscopic Investigation on Some Macrocyclic Complexes of Cu(II), Ni(II) and Co(II) - TIWARI, B.; SHARMA, N.K. (Asian Journal of Chemistry, 2010)
Transition metal complexes of Cu(II), Ni(II) and Co(II) with the macrocyclic ligands have been synthesized. These macrocyclic complexes were characterized on the basis of spectroscopic investigation using infrared spectra, electronic spectra and NMR spectra. Additional evidence for the structure of the macrocylic complexes have been collected from ESR spctra while conclusive evidence has been obtained from X-ray crystallography.